Tudományos irányítás(?) a nők és férfiak időfelhasználásában - Csehné Papp, Imola (Közép-Európai Közlemények, 2015)
Recently, an increasing number of international and domestic research focuses on examining the status of women in the labor market, women's career opportunities and feminisation some professions. Women should make a balance between family, career and leisure time, which is not an easy task.The aim of my research was to get to know the personal time management of the employees at the public sector. The study examined women working in the public sector and men's individual time use. The sample regarding this research was provided by 170 employees. The ‘balance of time’ was open, the filling of the questionnaires appened on a volunteer basis, therefore appreciable questionnaires were available from every region. The observation unit was one daily time usage of one person, i.e. one ‘humanday’. The research is based on the following hypothesis: in this case there is no fundamental difference between men and women in the use of time. The results only partially disproved the hypothesis, the main reason for the search for different roles.